Transient Hyperammonemia of the Newborn: A Case Study - Amir Kamal Hardani; Majid Aminzadeh (Mashhad University of Medical Sciences, 2018)
Background: Transient hyperammonemia of the newborn (THAN) is an overwhelming condition presenting with coma within 2-3 days of life and requiring immediate treatment. The etiology of this condition remains unknown. Duration of coma determines the degree of neurologic impairment and developmental delay in hyperammonemia. Case report: A newborn (BW=2900 g) was presented with a clear prenatal and perinatal medical history, poor sucking, refusal to feed, and deep coma within 72 hours of birth; the infant required ventilator assistance. On admission, physical examinations showed normal conditions, except for mild generalized weakness. Moreover, there was no history of consanguinity or maternal or obstetrics illnesses. However, the laboratory tests revealed marked hyperammonemia (plasma ammonia > 397 μg/dL, normal: 27-102 µg/dl) and elevated lactate (36.1 mg/dl, normal < 20 mg/dl). With aggressive therapy (no dialysis), he survived and was discharged without any complications.  The follow-up examinations during the next six months showed that his development was within the normal range without any signs of delay. Conclusion: Hyperammonemia should be considered in infants presenting with neurological deterioration as timely and appropriate intervention could result in good prognosis.